Blow fly artifacts from blood and putrefaction fluid on various surfaces: a source for forensic STR typing. Issue 3 (15th October 2015) - Kulstein, Galina; Amendt, Jens; Zehner, Richard
Abstract: Adult blow flies can deposit small spots ('artifacts') containing biological fluids like blood on various surfaces at a crime scene, either by regurgitation or defecation, and thereby create new or modify existing stains. These minute traces may represent evidence for the past presence of a certain person or victim in crime scene scenarios where nobody is present or all other crime‐related biological traces have been cleaned up. We analyzed artifacts on crime scene relevant surfaces (glass, wood, concrete, wallpaper, carpet, plastic wrap), produced by the forensically important blow fly Calliphora vicina Robineau‐Desvoidy (Diptera: Calliphoridae) after ingesting fresh and degraded porcine blood as well as putrefaction fluid from a pig's trotter and evaluated the potential of these spots for short tandem repeat (STR) analysis at various time intervals after deposition. Genotyping was possible on single fly artifacts on all surfaces up to 300 days after deposition by the flies after both blood or putrefaction fluid intake. The results indicate that the suitability for STR typing of those spots mainly depends on the time since deposition. The activity of flies at a crime scene can lead to artifacts which are – even 300 days after deposition – a valuable source of case‐related DNA. Sometimes those traces may even be the only source of information for DNA profiling.